Characteristic of pH and Temperature of Crude Extract of Glukoamilase from Gliocladium KE by using Solid Substrate of Sago Hampas - Risa Meutia Fiana; Novelina Novelina; Alfi Asben (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2022)
This  research  wasaimed  at  figuring  optimumpH and  temperature  of crude  enzyme  extract glukoamilase from  isolate Gliocladium  KEusing  substrate  of  solid  sago  hampas. The  research  wasconducted  by  two  phases,  first  wasfiguring  optimumpH and  second  was  optimum  temperature.  it  wasbased  on  Complete  Random  Design.  The  data  were  statistically  analyzed  by  using  F  test.  If  the  result showedsignificance  different,the  analysis  wascarried out by using Duncan’s New Multiple Range Test (DNMRT)  with  5%  tolerance.  The  result  showedthat  optimumpH ofcrude glukoamilaseextract  from sago hampas was optimumpH of glukoamilasefrom Gliocladium KE using solid substrate of sago hampas waspH 6,0  with  activity  of  enzyme  76,56  U/ml  with  final  product  of  solube  starch  0.09%,  the  level  of reducing  sugar  62,01%,  and  total  sugar  78,43%.  Optimum  temperature  was 60 ?C with enzyme activity 78,33 U/ml, final product of solube starch 0,13%, reducing sugar 63,04%, and total sugar 79,55%